2022
DOI: 10.3389/fonc.2022.897898
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome DNA Methylation Sequencing Reveals Epigenetic Changes in Myelodysplastic Syndromes

Abstract: Epigenetic dysregulation of cancer-associated genes has been identified to contribute to the pathogenesis of myelodysplastic syndromes (MDS). However, few studies have elucidated the whole-genome DNA methylation in the initiation pathogenesis of MDS. Reduced representation bisulfite sequencing was performed in five de novo MDS patients and four controls to investigate epigenetic alterations in MDS pathogenesis. The mean global methylation in five MDS patients showed no significant difference compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Analysis of a human 12K CpG microarray and GeneChips Human Genome U133 Plus 2.0 arrays by del Rey et al revealed 552 differentially methylated CpG loci and 1005 genes that significantly differed between low-risk MDS patients and the control group [23]. Zhou et al performed reduced representation bisulfite sequencing to investigate epigenetic alterations involved in the pathogenesis of MDS, identifying 1459 differentially methylated fragments, including 759 hypermethylated fragments and 700 hypomethylated fragments, between MDS patients and controls [24]. Lee et al applied a whole-genome-wide DNA microarray technique combined with Ingenuity Pathway Analysis to determine differential states of DNA methylation between RAEB and refractory cytopenia with multi-lineage dysplasia and identified 16 increased hypermethylation events specifically in RAEB samples [16].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of a human 12K CpG microarray and GeneChips Human Genome U133 Plus 2.0 arrays by del Rey et al revealed 552 differentially methylated CpG loci and 1005 genes that significantly differed between low-risk MDS patients and the control group [23]. Zhou et al performed reduced representation bisulfite sequencing to investigate epigenetic alterations involved in the pathogenesis of MDS, identifying 1459 differentially methylated fragments, including 759 hypermethylated fragments and 700 hypomethylated fragments, between MDS patients and controls [24]. Lee et al applied a whole-genome-wide DNA microarray technique combined with Ingenuity Pathway Analysis to determine differential states of DNA methylation between RAEB and refractory cytopenia with multi-lineage dysplasia and identified 16 increased hypermethylation events specifically in RAEB samples [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study demonstrated that LEP promoter hypermethylation in bone marrow MNCs was associated with inferior OS and could serve as an independent prognostic predictor in AML [ 30 ]. However, the same authors reported that LEP hypermethylation in bone marrow MNCs from MDS patients was associated with a longer survival time in MDS but without being an independent prognostic marker [ 29 ]. Our study suggests a worse prognosis in MDS patients with a high LEP promoter methylation at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The direct role of leptin in the initiation and progression of myeloid neoplasms is controversial and not fully understood. Several studies suggest a proliferative and/or anti-apoptotic effect of leptin on MDS [ 29 ] and AML [ 42 - 44 ] cells in vitro and one study suggests that leptin stimulates leukemic cell growth in vivo by stimulation of angiogenesis [ 45 ]. However, this is contradicted by the low or normal plasma leptin levels reported in several studies [ 34 - 39 ] and the LEP hypermethylation found in MDS patients in our study and reported by others [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations